Strategi Promosi Digital Usaha Mikro Keripik Incess dalam Memperluas Pemasaran Produk Menggunakan Analisis SWOT dan AHP - Safira Miranda; Dewi Kurniati; Anita Suharyani (Universitas Galuh, 2026)
This research aims to formulate an effective digital promotion strategy for the Incess Chips micro business in expanding the marketing reach of its products in Pontianak City. The background of this research is based on the low effectiveness of digital promotions run by Incise Chips, characterized by the lack of consumer involvement on various digital platforms such as Instagram, Facebook, and Shopee. This study uses a mixed method approach by combining SWOT analysis to identify internal and external factors, and the AHP (Analytical Hierarchy Process) method to determine the priority of promotion strategies. The results of the SWOT analysis show that Incess Chips are in quadrant I (aggressive strategy), with a coordinate value (X=0.94; Y=0.49), which indicates that the business can leverage internal strengths to pursue external opportunities to the fullest. This position shows that the current limited reach is not due to product quality, but to the lack of optimal market penetration. Furthermore, the results of the AHP calculation determined the priority strategy with the highest weight, namely SO1: digital marketing optimization by utilizing product quality and customer reviews (weight 0.37), followed by SO4: optimization of incubation programs in independent production, technology, and promotion (weight 0.34). Both strategies are considered to be able to increase business visibility, credibility, and competitiveness in a sustainable manner. Thus, this research contributes to the preparation of a directed and systematic analysis-based digital promotion strategy in order to encourage growth.